Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s00428-006-0342-y
|View full text |Cite
|
Sign up to set email alerts
|

Activation of extracellular regulated kinases (ERK1/2) but not AKT predicts poor prognosis in colorectal carcinoma and is associated with k-ras mutations

Abstract: Signal transduction and modulation represent central mechanisms in cellular processes such as cell-cycle regulation, oncogenesis, and apoptosis. The aim of this study was to determine the prognostic relevance of two kinases important in the regulation of cell proliferation and apoptosis in 135 colorectal cancer cases: AKT and extracellular regulated kinases (ERK1/2). We investigated the relationship of phospho-ERK1/2 (pERK1/2) and phospho-AKT (pAKT) with associated parameters (EGFR, COX-2, cyclin-D1), prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 44 publications
4
50
4
Order By: Relevance
“…Moreover it seems as if both kinases show different subcellular localizations in various human carcinomas. In a colon cancer study, we showed pAKT immuno-localization in the nucleus and cytoplasm [6] , in contrast to our results in ICC with a restricted immunoreactivity in the cytoplasm.…”
Section: Pathwaycontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover it seems as if both kinases show different subcellular localizations in various human carcinomas. In a colon cancer study, we showed pAKT immuno-localization in the nucleus and cytoplasm [6] , in contrast to our results in ICC with a restricted immunoreactivity in the cytoplasm.…”
Section: Pathwaycontrasting
confidence: 99%
“…Phosphorylation of proteins either on specific tyrosine or serine residues is a posttranslational event modulating the activity of many key signaling molecules in the cell including AKT and ERK1/2 [4] . We recently demonstrated AKT and ERK phosphorylation as an independent prognostic parameter in breast cancer and colorectal cancer, respectively [5,6] . Others found an association of AKT [5,[7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…In instances of coincident activation of the RAF and PI3K pathways, combinations of AZD6244 and PI3K/mTOR inhibitors may prove efficacious. 52 It is also important to stress that ERK1/2 activation did not simply correlate with the presence of a KRAS mutation; in some cells KRAS coupled well to ERK1/2 and in others poorly and this is also seen in human tumour samples 53,54 and mouse models. 55,56 This differential coupling to downstream effectors represents a challenge and suggests that biochemical analysis should be combined with mutational profiling in interpreting patient responses and informing patient recruitment to trials.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in agreement with several larger colorectal cancer prognostic studies. 23,[32][33][34] Lymph node expression of pERK and MUC1 and loss of p16 expression also were identified as independent features of poor outcome. In particular, p16 appeared to play a more important role in predicting prognosis than any other marker, including pERK, in both primary tumors and lymph node metastases.…”
Section: Original Article 4480mentioning
confidence: 97%